Incomplete sulphomucin-secreting intestinal metaplasia for gastric cancer. Preliminary data from a prospective study from three centres. Issue 12 (December 1985) - Filipe, M I; Potet, F; Bogomoletz, W V; Dawson, P A; Fabiani, B; Chauveinc, P; Fenzy, A; Gazzard, B; Goldfain, D; Zeegen, R
Abstract : A joint prospective long term study of gastric biopsies has been undertaken to survey intestinal metaplasia Types I, II, and III in terms of their incidence, distribution and value in the selection of high risk cancer patients. This study is based on protocols agreed between three centres for endoscopy, histological interpretation, and mucin histochemistry. The results on the first 1350 gastric biopsies examined during 1981-1982 are presented. Intestinal metaplasia was found in 267 biopsies (20%), being common in association with carcinoma (71%), less so in benign conditions such as gastric ulcer (39%), and chronic gastritis (24%), but rare in 'normal' (3%). Type I intestinal metaplasia was predominant (73%) in all the biopsies with intestinal metaplasia and was most common in benign conditions, 70% in gastric ulcer and 76% in chronic gastritis. Type III intestinal metaplasia (incomplete sulphomucin-secreting intestinal metaplasia) was recorded in only 9.8% of all the biopsies with intestinal metaplasia and had a higher incidence in carcinoma (35%), than in benign conditions (7%) (p less than 0.0001). These results suggest that intestinal metaplasia types may have different malignant potential and their identification may be useful in screening patients for early detection of cancer.